(untitled) (Research, Society and Development, 2020)
Youth and Adult Education (EJA) is a specific modality of Basic Education aimed at the school inclusion of a public that was excluded from education during their childhood or adolescence. In this perspective, a study was developed whose objective is to identify the factors that contribute to the persistence and school dropout of students from EJA in the northeast, Castanhal-PA and propose actions for the permanence of EJA students. The locus of the research consisted of three municipal schools located in peripheral neighborhoods, which also have students from the countryside. The research was qualitative and quantitative, carried out with students, teachers, managers and education specialists. Quantitative data were acquired through on-site research and qualitative data through interviews and socioeconomic questionnaires. Among the predicted variables of the reason for the evasion of EJA students at school, low marks stand out, lack of interest, illness, work, among others; the variables diagnosed as the reason for the persistence of these students, among others, were: learning to read and write, developing the ability to solve problem situations and the search for professional qualification. It was found that social variables have a significant impact on students’ persistence and / or dropout.